The effect of biomaterial selection on the static strength of femur prosthesis - Kural, Saim (Array, 2018)
Throughout the history, biomaterials have been widely used for replacing damaged human organs. Biocompatibility is generally defined as the harmony of the biomaterials with human body physically, chemically and biologically. Mechanical strength properties are of great importance in biocompatibility of the biomaterials which are used as orthosis and prosthesis in skeletal system. In this study, static analyses of femur implants which were modelled by using 316 stainless steel and Ti6Al4V titanium alloy, were carried out under three different axial forces (500, 750 and 1000 N). As a result of the analyses made, the effect of material selection on the biomechanical and biocompatibility properties of femoral implants was determined.